Evaluation of the success of hysteroscopic uterine septum resection - Sule Atalay Mert; Berna Dilbaz; Funda Akpinar; Elif Gulsah Diktas; Tugba Kinay; Tugba Ensari; Ozlem Moraloglu Tekin (Wolters Kluwer Medknow Publications, 2023)
Objectives: The aim is to use three-dimensional transvaginal ultrasonography (3-D TVUS) to evaluate the success of hysteroscopic metroplasty for the uterine septum and to compare the pregnancy outcomes. Materials and Methods: Thirty-eight patients with uterine septum who had hysteroscopic uterine septum resection were recruited. Preoperative 3-D TVUS measurements of the septal apex to the uterine fundus (s1), septal apex to internal os distance (s2), and intercornual distance (s3) were compared with the postoperative values. The pregnancies of the patients were followed up for a year postoperative period. Results: Out of the 38 patients, thirty-five had partial uterine septum (class U2a), while 3 patients had complete uterine septum (class U2b). Eighteen (47.36%) of the patients who underwent uterine septum resection achieved pregnancy, and thirteen of these pregnancies were (72.2%) term pregnancies, and all term pregnancies resulted in a live birth. Natural conception was achieved in 77.7% (14 of 18) of the patients. Term pregnancy occurred in 68.7% (11 of 16) of the patients with a partial septum and in 66.6% (2 of 3) of the patients with a complete uterine septum. A comparison of the 3-D TVUS measurements of the uterus pre- and postoperatively showed a decrease in s1 and an increase in s2 (P < 0.05). The uterine cavity length of pregnant patients was found to be higher than nonpregnant patients (P < 0.05). Conclusion: Reproductive results of hysteroscopic metroplasty were favorable in achieving live and term birth. three-dimensional TVUS can be preferred as a noninvasive effective method in objective evaluation of the success of the hysteroscopic surgery.